2021
DOI: 10.1186/s12939-021-01446-x
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year trends in self-reported racism and link with health and well-being of African Canadian adolescents: a secondary data analysis

Abstract: Background We assessed the prevalence and trends in racial discrimination among African Canadian adolescents in British Columbia. The association between racial discrimination and self-rated health, access to mental health services, substance use, suicidal thoughts and attempts, experience of extreme stress, among others were examined within the 2018 dataset. Methods Secondary analysis used the data collected from African Canadian adolescents (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…However, the lifetime prevalence rates of PRD among the CDC sample were notably higher than those reported over the past year from high schoolers in our study (35.6% versus 7.3%, respectively), possibly due to differences in the time period for which PRD was measured [47]. Consistent with the existing epidemiological and clinical literature, PRD was significantly associated with an increased likelihood of serious psychological distress, suicidal ideation, and suicide attempt across the entire sample and each racial/ethnic group [5,[18][19][20]35,36,[43][44][45][46][47]. As with the aforementioned 2021 CDC study, these results remained consistent even after controlling for other known demographic risk factors for suicide such as SOGI and rurality, though the strength of association between PRD and suicidality in the current study was larger in magnitude than the results of the CDC analysis [5].…”
Section: Key Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…However, the lifetime prevalence rates of PRD among the CDC sample were notably higher than those reported over the past year from high schoolers in our study (35.6% versus 7.3%, respectively), possibly due to differences in the time period for which PRD was measured [47]. Consistent with the existing epidemiological and clinical literature, PRD was significantly associated with an increased likelihood of serious psychological distress, suicidal ideation, and suicide attempt across the entire sample and each racial/ethnic group [5,[18][19][20]35,36,[43][44][45][46][47]. As with the aforementioned 2021 CDC study, these results remained consistent even after controlling for other known demographic risk factors for suicide such as SOGI and rurality, though the strength of association between PRD and suicidality in the current study was larger in magnitude than the results of the CDC analysis [5].…”
Section: Key Findingssupporting
confidence: 83%
“…In a national cross-sectional survey in New Zealand, associations were demonstrated between perceptions of racial and ethnic discrimination experienced by indigenous and minority students and the experience of negative health and well-being outcomes such as depressive symptoms, substance misuse, feeling safe, and achievement [44]. Among African Canadian adolescents in British Columbia, annual surveys conducted between 2003 and 2018 found that PRD had gradually increased over that period; girls and immigrant African Canadians were most likely to have experienced discrimination, while adverse mental health outcomes associated with PRD varied across population subgroups (immigrant African Canadians and Black males were most likely to experience negative and persistent mental health problems) [45].…”
Section: Epidemiological Researchmentioning
confidence: 99%
“…Given that certain groups are more exposed to RD and RD has negative consequences for psychological well-being, studies began to investigate whether RD is associated with suicidal ideation (SI) and with a history of suicide attempt (SA). Several studies reported a positive association between RD and SI or SA across racially diverse groups in the U.S. ( Chao et al, 2012 ; Choi et al, 2020 ; Galán et al, 2021 ; Perez-Rodriguez et al, 2014 ; Walls et al, 2007 ), among Blacks in Brazil ( Santana et al, 2007 ) and Canada ( Okoye & Saewyc, 2021 ), Aboriginals in Australia ( Priest et al, 2011 ), Māori in New Zealand ( Williams et al, 2018 ), and ethnic minorities in China ( Pan & Spittal, 2013 ). As of yet, the only published meta-analysis investigating the association between RD and suicidality reported an association between the two phenomena ( r = −0.16; Paradies et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 As examples, the cost of transportation, poor health literacy, racial and gender discrimination, or the lack of translation services can all limit or inhibit access to health services. 6 Thus, population health, defined as “the health outcomes of a group of individuals, including the distribution of such outcomes within the group,” 7 (p.381) is deeply connected to the social and structural conditions in which people are born, work, live, and age, as well as to health equity. 8 …”
Section: Introductionmentioning
confidence: 99%